THE IMPACT OF KPIS ON OPERATIONAL EFFICIENCY AND COMPETITIVE ADVANTAGE IN TRADING ENTERPRISES - Іhor Rekunenko; Iana Kobushko; Roman Shubenko (Соціальна економіка)
This study investigates the impact of key performance indicators on operational efficiency and competitive advantage in trading enterprises, using secondary data and econometric modeling. Analyzing data from 50 firms across seven countries over a five-year period (2019-2023), the research employs a panel data regression model to assess how various KPIs influence operational outcomes and market positioning. The results reveal that KPIs related to productivity, cost management, and quality control significantly enhance operational efficiency and competitive advantage. Additionally, firm size and market conditions are found to moderate these relationships, highlighting the importance of contextual factors in KPI effectiveness. The results of the study show that KPIs are effective tools for optimizing operational processes. Firms with high KPIs achieve a better competitive position in the market, reinforcing the notion that well-managed KPIs significantly contribute to a firm's ability to outperform competitors. This study contributes to the academic understanding of KPI impact by confirming established theories and introducing new insights into the role of external factors. Practically, the findings offer actionable recommendations for trading enterprises to optimize their KPI frameworks, suggesting that tailored KPI strategies can lead to substantial improvements in performance and market success. The study underscores the critical role of KPIs as strategic tools for enhancing firm performance and maintaining a competitive edge in the global market. The research's limitations include the relatively small sample size and limited time frame, which suggest the need for further studies to validate and extend these findings. Trading companies must constantly improve their KPI strategies to adapt to changing conditions and maximize their benefits, ensuring they remain leaders in their industries.